Structural response of metal sheets under combined shear and tension. (August 2020) - Kumar, Amit; Singha, M.K.; Tiwari, Vikrant
Abstract: The structural response of metal sheets under various in-plane loads are investigated in this article using a combined experimental and numerical approach. For this purpose, four different specimen shapes, made from 2 mm thin sheets of aluminum (AL1100) and mild steel (IS 1570), are tested at different loading angles, e.g., pure shear (0°), pure tension (90°) and mixed mode (30°, 60°) in the Arcan fixture. Both the full field displacement and full field strain profiles of the gauge section are investigated using the stereo imaging (3D DIC). The possibility of achieving the ultimate shear strength in the specimen or the plastic buckling (out-of-plane deformation) of the specimen during the in-plane shear test is explored at the beginning. In the absence of out-of-plane deformation, the material behavior is studied at different loading angles, while the other sets of experiments are focused towards understanding the structural behavior of thin metal sheets. The experimental observations are also compared with the finite element simulation and excellent similarity is observed.